miRNAs modified by dietary lipids in Caco-2 cells. A microarray screening - Daimiel, Lidia (Genom Data, 2015)
We performed a screening of miRNAs regulated by dietary lipids in a cellular model of enterocytes, Caco-2 cells. Our aim was to describe new lipid-modified miRNAs with an implication in lipid homeostasis and cardiovascular disease [1], [2]. For that purpose, we treated differentiated Caco-2 cells with micelles containing the assayed lipids (cholesterol, conjugated linoleic acid and docosahexaenoic acid) and the screening of miRNAs was carried out by microarray using the μParaflo®Microfluidic Biochip Technology of LC Sciences (Huston, TX, USA). Experimental design, microarray description and raw data have been made available in the GEO database with the reference number of GSE59153. Here we described in detail the experimental design and methods used to obtain the relative expression data.